Zebrafish as a Model to Study the Role of Peroxisome Proliferating-Activated Receptors in Adipogenesis and Obesity - Marjo J. Den Broeder; Victoria A. Kopylova; Leonie M. Kamminga; Juliette Legler (PPAR Research)
The Peroxisome Proliferator-Activated Receptors (PPARs) PPARA and PPARD are regulators of lipid metabolism with important roles in energy release through lipid breakdown, while PPARG plays a key role in lipid storage and adipogenesis. The aim of this review is to describe the role of PPARs in lipid metabolism, adipogenesis, and obesity and evaluate the zebrafish as an emerging vertebrate model to study the function of PPARs. Zebrafish are an appropriate model to study human diseases, including obesity and related metabolic diseases, as pathways important for adipogenesis and lipid metabolism which are conserved between mammals and fish. This review synthesizes knowledge on the role of PPARs in zebrafish and focuses on the putative function of PPARs in zebrafish adipogenesis. Using in silico analysis, we confirm the presence of five PPARs (pparaa, pparab, pparda, ppardb, and pparg) in the zebrafish genome with 67–74% identity to human and mouse PPARs. During development, pparda/b paralogs and pparg show mRNA expression around the swim bladder and pancreas, the region where adipocytes first develop, whereas pparg is detectable in adipocytes at 15 days post fertilization (dpf). This review indicates that the zebrafish is a promising model to investigate the specific functions of PPARs in adipogenesis and obesity.